Delirium risk factors analysis post proximal femur fracture surgery in elderly - Leigheb, Massimiliano; de Sire, Alessandro; Zeppegno, Patrizia; Forni, Francesca; Sgreccia, Massimo; Gagliardi, Vincenzo Pio; Pogliacomi, Francesco; Sabbatini, Maurizio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The increase in the average-age and in the percentage of elderly people implies an exponential increase in fractures of the proximal femur. A common consequence of hip fracture in elderly patients is delirium, characterized by cognitive confusion or a lethargic-type condition. Predisposing factors have been identified, but risk factors assessment useful for managing clinical intervention, has not received unanimous consent. This work aims to identify the potential risk factors for delirium in the elderly operated for hip fracture.Methods: In this prospective observational study, we included 83 patients aged ≥65 years. Patients undergoing osteosynthesis of the femur and hip replacement for fractures were included. Patients already delusional in the pre-operative period were excluded. At the time, deadlines T0 (pre-operative), and T1,T3,T7 post-operative day, delirium, hematic parameters, blood transfusions, were assessed.Results: Level of delirium was assessed obtaining 80% not delusional and 20% delusional. Glycemia and hemoglobin were not found to be risk factors, although they are known to influence cognitive status; we hypothesize they should be considered predisposing factors. Comorbidities such as atrial fibrillation and Chronic Obstructive Pulmonary Disease were found associated with delirium. The most advanced age, anxiolytic drugs, the use of benzodiazepine as anaesthetic, the time surgical waiting, were found significantly associated with delirium.Conclusions: Taken together, findings of this prospective observational study showed that environmental and metabolic risk factors might contribute to make elderly susceptible to develop postoperative delirium following hip surgery. Thus, these patients should be adequately assessed and monitored. (www.actabiomedica.it)